A true fiber optic refractometer. Issue 1 (5th January 2017) - Zhou, Wenjun; Zhou, Yan; Albert, Jacques
Abstract : Knowledge of the exact value of the refractive index of liquids is increasingly required in new optofluidic applications where light is guided or modified by fluids. Measurements of the wavelengths of the multiple cladding mode resonances in a tilted fiber Bragg grating provide a calibration of the fiber properties that further allow the precise determination of the refractive index of any liquid in which the fiber is immersed. Abstract: The best instrument to measure the refractive index of liquids is the Abbe refractometer which can only provide accuracies of the order of 10 −5 at visible wavelengths and 10 −4 in the near infrared. Here we present a technique by which the exact wavelength positions in the near infrared frequency comb of a tilted grating inscribed in the core of an optical fiber can be used to measure the absolute value of the refractive index of a liquid in which the fiber is inserted, with an accuracy of ±5×10 −5 . This is in contrast to typical fiber optic‐based "refractometry" where only refractive index variations can be measured accurately, hence the appellation of "true" fiber optic refractometer here. In addition to the increased accuracy, the fiber refractometer proposed here offers the additional advantages associated with in situ measurements. The performance of this refractometer is demonstrated by measurements in water from room temperature down to near freezing at wavelengths in the 1550 nm window.